Religion, ethnicity, and citizenship: the role of Jain institutions in the social incorporation of young Jains in Britain and the United States - Shah, Bindi V. (Journal of contemporary religion, 2017)
The on-going importance of religion as a marker of identity among young South Asians has provoked reflection on the relationship between religion and citizenship in the aftermath of events such as 9/11 and 7/7. In general, European and American scholarship highlights different perspectives on the role of religion in the social incorporation of immigrants and their children. In this article I explore how religion shapes identity and citizenship among young Jains, a group that experiences successful socio-economic integration and material success in Britain and the United States. This qualitative comparative analysis of Jain institutions which are oriented towards young Jains reveals the ways in which the intersection of transnational circulation of religious ideas and actors, national integration regimes, migration histories, and the place of religion in specific contexts shapes religious identities, religious group boundaries, and religious discourses in different ways. Different Jain religious assemblages affirm views of religion in the United States as having a positive role in the social incorporation of immigrants and their children, but point to a more neutral role for religion in the incorporation of middle-class young Jains in Britain.